Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To compute the limit [tex]\(\lim_{x \rightarrow 1} \frac{\frac{1}{x+2} - \frac{1}{3}}{x-1}\)[/tex], we start by analyzing the given expression step-by-step.
First, consider the function:
[tex]\[ f(x) = \frac{\frac{1}{x+2} - \frac{1}{3}}{x-1} \][/tex]
We need to find [tex]\(\lim_{x \rightarrow 1} f(x)\)[/tex].
The expression inside the limit can be simplified. Combine the terms in the numerator:
[tex]\[ \frac{1}{x+2} - \frac{1}{3} = \frac{3 - (x+2)}{3(x+2)} = \frac{3 - x - 2}{3(x+2)} = \frac{1 - x}{3(x+2)} \][/tex]
Thus, the function becomes:
[tex]\[ f(x) = \frac{\frac{1 - x}{3(x+2)}}{x-1} \][/tex]
This simplifies to:
[tex]\[ f(x) = \frac{1 - x}{3(x+2)(x - 1)} \][/tex]
Notice that the numerator [tex]\(1 - x\)[/tex] is [tex]\(-(x - 1)\)[/tex]. Substitute this in:
[tex]\[ f(x) = \frac{-(x - 1)}{3(x+2)(x - 1)} \][/tex]
Cancel the common term [tex]\((x - 1)\)[/tex] in the numerator and the denominator:
[tex]\[ f(x) = \frac{-1}{3(x + 2)} \][/tex]
Now, find the limit as [tex]\(x\)[/tex] approaches 1:
[tex]\[ \lim_{x \rightarrow 1} f(x) = \lim_{x \rightarrow 1} \frac{-1}{3(x + 2)} \][/tex]
Substitute [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = \frac{-1}{3(1 + 2)} = \frac{-1}{3 \cdot 3} = \frac{-1}{9} \][/tex]
The limit is:
[tex]\[ \lim_{x \rightarrow 1} \frac{\frac{1}{x+2} - \frac{1}{3}}{x-1} = \frac{-1}{9} \][/tex]
This result is [tex]\(-\frac{1}{9}\)[/tex]. Converting this fraction to a decimal:
[tex]\[ -\frac{1}{9} \approx -0.1111 \][/tex]
Thus, the best answer from the given choices is:
a. [tex]\(\lim_{x \rightarrow 1} f(x) = -0.1111\)[/tex]
So, the correct answer is:
a. [tex]\(\lim_{x \rightarrow 1} f(x) = -0.1111\)[/tex]
First, consider the function:
[tex]\[ f(x) = \frac{\frac{1}{x+2} - \frac{1}{3}}{x-1} \][/tex]
We need to find [tex]\(\lim_{x \rightarrow 1} f(x)\)[/tex].
The expression inside the limit can be simplified. Combine the terms in the numerator:
[tex]\[ \frac{1}{x+2} - \frac{1}{3} = \frac{3 - (x+2)}{3(x+2)} = \frac{3 - x - 2}{3(x+2)} = \frac{1 - x}{3(x+2)} \][/tex]
Thus, the function becomes:
[tex]\[ f(x) = \frac{\frac{1 - x}{3(x+2)}}{x-1} \][/tex]
This simplifies to:
[tex]\[ f(x) = \frac{1 - x}{3(x+2)(x - 1)} \][/tex]
Notice that the numerator [tex]\(1 - x\)[/tex] is [tex]\(-(x - 1)\)[/tex]. Substitute this in:
[tex]\[ f(x) = \frac{-(x - 1)}{3(x+2)(x - 1)} \][/tex]
Cancel the common term [tex]\((x - 1)\)[/tex] in the numerator and the denominator:
[tex]\[ f(x) = \frac{-1}{3(x + 2)} \][/tex]
Now, find the limit as [tex]\(x\)[/tex] approaches 1:
[tex]\[ \lim_{x \rightarrow 1} f(x) = \lim_{x \rightarrow 1} \frac{-1}{3(x + 2)} \][/tex]
Substitute [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = \frac{-1}{3(1 + 2)} = \frac{-1}{3 \cdot 3} = \frac{-1}{9} \][/tex]
The limit is:
[tex]\[ \lim_{x \rightarrow 1} \frac{\frac{1}{x+2} - \frac{1}{3}}{x-1} = \frac{-1}{9} \][/tex]
This result is [tex]\(-\frac{1}{9}\)[/tex]. Converting this fraction to a decimal:
[tex]\[ -\frac{1}{9} \approx -0.1111 \][/tex]
Thus, the best answer from the given choices is:
a. [tex]\(\lim_{x \rightarrow 1} f(x) = -0.1111\)[/tex]
So, the correct answer is:
a. [tex]\(\lim_{x \rightarrow 1} f(x) = -0.1111\)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.